NK-1 Receptor Antagonists and Pruritus: Review of Current Literature - Marcelina Pojawa-Gołąb; Kamila Jaworecka; Adam Reich (Adis, Springer Healthcare, 2019)
Abstract The discovery of the first neurokinin 1 (NK-1) receptor antagonist was a turning point in the prevention of chemotherapy-induced nausea and vomiting. The NK-1 antagonists are a novel class of drugs that possess antidepressant, anxiolytic, and antiemetic properties. Recently, clinicians have also described an anti-itch activity of NK-1 antagonists. We present herein results from currently available data on use of NK-1R antagonists in dermatology. For this purpose, a systemic electronic literature search of the PubMed and CINAHL databases, Cochrane Library, and clinicaltrials.gov website was performed. Based on currently available data, it can be concluded that NK-1 inhibitors show significant antipruritic potential for treatment of chronic pruritus in different dermatological conditions, but further studies are needed to establish the best indications and dosage of these drugs.